Gonad maturity of simping Placuna placenta, Linn 1758 (Bivalve: Placunidae) harvested from Kronjo Coastal, Indonesia - Yonvitner, Yon; Setyobudiandi, Isdradjad; Dahuri, Rokhmin; Jamilah, Jamilah (Aceh Journal of Animal Science, 2020)
Simping (P. placenta) is a coastalresourcefoundin shallow water with amuddysubstrate.Simping widely used as a source of food and as raw material for the decoration.Utilization ofsimpinguntil now has not yetfocusedonrecruitment, reproductive aspect. This information is important as abasisdata for determining the size of thesimpingcatch. This study aimed to find out about of reproduction aspect, determining sex ratio the size of the catchsimping.This research was conduct for three months at 3 locations.The number of samples in the analysis is 36 species to determine sex ratio and gonad maturity.Sex ratio indifferent from male and female, but based on thetimesex ratio ofsimping significant,both male and female. The lengthsize of gonads shellfish matures form 5.50 cm and 5.85 cm at 2 TKG conditions. Length ofsimpingmature from 6.08 cm, 6.24 cm, 6.45 cm and 7.11 cm dominant at TKG mature stage 3,and 8.61 cm dominant at 4 TKG conditions. Sex ratioreaches6 cm shell length and not significant between males and females (M: F=1;1).It is concluded that thelevel of maturity of gonads increases with increasing of simping size.